Effects of a Diet Enriched with Polyunsaturated, Saturated, or Trans Fatty Acids on Cytokine Content in the Liver, White Adipose Tissue, and Skeletal Muscle of Adult Mice - Bruno dos Santos; Debora Estadella; Ana Cláudia Losinskas Hachul; Marcos Hiromu Okuda; Mayara Franzoi Moreno; Lila Missae Oyama; Eliane Beraldi Ribeiro; Claudia Maria da Penha Oller do Nascimento (Mediators of Inflammation)
This study analyzed the effect of diet enriched with 30% lipids on cytokines content in different tissues. Swiss male mice were distributed into four groups treated for 8 weeks with control (C, normolipidic diet); soybean oil (S); lard (L); and hydrogenated vegetable fat (H). We observed an increase in carcass fat in groups S and L, and the total amount of fatty deposits was only higher in group L compared with C group. The serum levels of free fatty acids were lower in the L group, and insulin, adiponectin, lipid profile, and glucose levels were similar among the groups. IL-10 was lower in group L in mesenteric and retroperitoneal adipose tissues. H reduced IL-10 only in retroperitoneal adipose tissue. There was an increase in IL-6 in the gastrocnemius muscle of the L group, and a positive correlation between TNF-α and IL-10 was observed in the livers of groups C, L, and H and in the muscles of all groups studied. The results suggested relationships between the quantity and quality of lipids ingested with adiposity, the concentration of free fatty acids, and cytokine production in white adipose tissue, gastrocnemius muscle, and liver.